The Impact Of Suggestopedia Method On Students' Writing Achievement: A Gender-Based Analysis - Sunengko, Sunengko; Nurfaisal, Nurfaisal (Jompa Research and Development, 2024)
Enhancing students' writing skills is a crucial aspect of quality learning. The primary objective of this quasi-experimental study is to examine the impact of the suggestopedia method in contrast to traditional instructional approaches, while also assessing the influence of gender on students' writing achievement and the potential interaction between instructional approach and gender. The study took place at SMAN 1 Nganjuk, with the participation of 36 students in the experimental group and 35 students in the control group. Among the participants, there were 58 female students and 18 male students. Data analysis using SPSS revealed a significant difference in average scores, with the experimental class averaging 83.34 and the control class averaging 79.41, resulting in a mean difference of 3.93. The significance level of .05 indicated that the suggestopedia method was more effective than the conventional approach. Moreover, when considering the entire cohort of 53 female and 18 male students, a significant difference of 6.13 or approximately 7.98% was observed, favoring female students' writing performance. However, the analysis of variance demonstrated a significance value of 0.551, which exceeds the 0.05 threshold, leading to the conclusion, that the findings indicate a lack of interaction between the learning models and gender in relation to the writing outcomes of the students.